Muscle protein turnover in endurance training: a review - Seene, T.; Kaasik, P.; Alev, K. (International Journal of Sports Medicine, 2011)
There has been much debate about skeletal muscle capacity to adapt to long-lasting endurance exercise. Exercise in the aerobic zone of metabolism does not result in hypertrophy of skeletal muscle fibres but increases their oxidative capacity. The duration and intensity of an exercise session determines the time period of depressed muscle protein synthesis and increased degradation rate during the recovery period after exercise. Protein turnover characterizes the renewal processes of muscle proteins and the functional capacity of muscle. The turnover rate of myofibrillar proteins is slow in comparison with mitochondrial proteins and depends on the oxidative capacity of muscle fibres. The turnover rate of myofibrillar proteins in the same muscle is different and is also different within the myosin molecule between myosin heavy and light chain isoforms. The turnover rate of muscle proteins in endurance training shows the adaptation of skeletal muscle to long-lasting exercise via remodelling of muscle structures. Adaptational coordination between myofibrillar and mitochondrial compartments shows the physiological role and adaptational capacity of skeletal muscle to endurance training. It is challenging to use muscle protein turnover for the purposes of monitoring the training process of endurance athletes, optimizing training programs and preventing overtraining.